Vocabulary Retention as a Meaning-Making Process: Evidence from EFL Cadets in a Structured Learning Environment - Althaf Fina Cahyani; Sonny Elfiyanto; Ira Maria Fran Lumbanbatu (Al-Qalam Institute, 2026)
Vocabulary retention remains a central concern in EFL learning, particularly in contexts where exposure to English is limited and often confined to structured classroom environments. This study examines how reading comprehension functions as a basis for vocabulary retention among cadets at Poltekad Batu. Adopting a qualitative case study design, the research explores learners’ experiences in engaging with English texts, focusing on how they interpret unfamiliar vocabulary through contextual cues, apply reading strategies, and gradually retain lexical items over time. Data were collected through in-depth interviews with cadets and instructors, supported by field-based documentation, and analyzed using a thematic approach. The findings reveal that vocabulary retention is not driven by memorization alone but emerges from a dynamic process involving comprehension, repeated exposure, and contextual interpretation. Learners tend to prioritize understanding the overall meaning of texts before focusing on individual words, using strategies such as inferencing, re-reading, and note-taking to reinforce retention. In addition, the study highlights how prior knowledge and situational context shape meaning construction, particularly within a military-based learning environment. These findings suggest that vocabulary learning is more effective when embedded in meaningful reading activities, carrying implications for transformative education in which comprehension-driven instruction fosters learner autonomy and reflective meaning construction in structured EFL contexts